2020
DOI: 10.17220/ijpes.2020.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Relationship between Adolescents’ Subjective Well-Being and Parenting Styles and Smartphone Addiction by Several Variables.

Abstract: Aim of this research is to examine the relationship between adolescents' subjective well-being and parenting style and smartphone addiction by several variables. The research population was composed of high school students studying in Kocaeli province in the academic year of 2017-2018. The sample was composed of 671 adolescents attending 6 different high schools which were randomly chosen out of this population. 313 (46.6%) of the participants are female, 358 (53.4%) of them are male. Relational survey model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Aljomaa et al (2016) and Mohammadbeigi et al (2016) stated that male students were addicted more, while Bal and Balcı (2020), Gündoğmuş, Taşdelen Kul and Çoban (2020) and Celikkalp et al (2020) stated that female students were addicted more. In some studies, no significant difference was found in terms of gender (Kula et al, 2020;Yıldırım and Ayas, 2020;Minaz and Çetinkaya Bozkurt, 2017;Kumcagiz and Gündüz, 2016). In the context of the sample examined, it is thought that this result stems from the fact that male students spend more time in using smartphones than female students, and differences in their intended use.…”
Section: Conclusion and Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Aljomaa et al (2016) and Mohammadbeigi et al (2016) stated that male students were addicted more, while Bal and Balcı (2020), Gündoğmuş, Taşdelen Kul and Çoban (2020) and Celikkalp et al (2020) stated that female students were addicted more. In some studies, no significant difference was found in terms of gender (Kula et al, 2020;Yıldırım and Ayas, 2020;Minaz and Çetinkaya Bozkurt, 2017;Kumcagiz and Gündüz, 2016). In the context of the sample examined, it is thought that this result stems from the fact that male students spend more time in using smartphones than female students, and differences in their intended use.…”
Section: Conclusion and Discussionmentioning
confidence: 93%
“…When the smartphone addiction levels of university students were analyzed according to the average daily smartphone usage time, it was observed that the students with high smartphone usage also had high addiction levels. Researches also showed that the usage of smartphones, which covers the daily duration of smartphone use and how many times a smartphone is checked, has a significant effect on smartphone addiction (Yıldırım and Ayas, 2020;Gökçearslan et al 2016). Students' fear of not being online and losing communication causes students to be busy with their smartphones for longer periods of time.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study (Yildirim & Ayas, 2020) aimed to reveal the relationship between psychological well-being, parenting pattern (parenting), and smartphone addiction among school students in Kocaeli province in Turkey. The sample consisted of 671 male and female students in the secondary stage, who are studying in six different secondary schools, who were randomly selected; a smartphone addiction scale, psychological well-being scale, and parenting pattern scale were applied to them.…”
Section: Studies Related To Patterns Of Parental Treatment and Emotio...mentioning
confidence: 99%
“…In addition, some studies examined emotional balance independently in Arab and foreign environments and on various samples, primary and secondary, university stage and on mothers, or with other variables such as the study (Yagnik, 2013;Kumar & Al-Tamawi, 2017;Hamad, 2019). As for the studies that dealt with the methods of parental treatment and its relationship to emotional balance, they were on older ages, such as high school and university students, and in different environments, such as the study of Al-Khouribi (2002), Ibraim (2011, Amara and Bouisha (2013), Al-Rawahieh (2016), Al-Tamawi (2020 and Al-Qaisi (2020) and Yildirim and Ayas (2020), and some of them are on verbally striking children, such as the study of Al-Ghadani (2014).…”
Section: Commenting On Previous Studiesmentioning
confidence: 99%